Spectrophotometric Determination of 2-Mercaptobenzothiazole in Cooling Water System - Mosaferi, Fazael; Delijani, Farid; Ekhtiary Koshky, Fateme (Asian Journal of Chemistry, 2010)
The simple and convenient determination of 2-mercaptobenzothiazole (MBT) with copper(II) in cetyltrimethylammonium bromide (CTAB) media has been studied. The UV-visible spectrum of Cu(II)-MBT complex in CTAB media had a good sensitivity and reproducibility. The Cu(II)-MBT complex in CTAB solution is stable at pH 9.0 and could be quantitatively complexed if Cu were added to the sample solution more than 125 equivalent of MBT (to the mol). The optimum concentration of CTAB was 0.01 %. The calibration curve of Cu(II)-MBT complex with good linearity (R2 = 0.9995) was obtained at the concentration range between 2.9 × 10-6 and 2.9 × 10-5 M in 0.01 % CTAB media. The detection limit was 9.7 × 10-7 M (0.162 mg L-1). 2-Mercaptobenzothiazole in water cooling of tabriz thermal power plant could also be determined. Based on the experimental results, this proposed technique cold be applied to the simple and convenient determi-nation of 2-mercaptobenzothiazole in real samples.